Mathematical Sorcery- Revealing the Secrets of Numbers - Clawson, Calvin C (New Delhi Viva Books Pvt. Ltd, 2004)
The secret of constellations, the enigma of the golden mean, and the brilliance of a proof are are just some of the breakthroughs Clawson explores with unbridled delight in this recreational math book. Throughout the book he divulges the wisdom of the ancient Greeks, Sumerians, Babylonians, and Egyptians, whose stunning revelations still have deep meaning today. Taking us beyond simple appreciation, Clawson urges us to tackle functions, tangents, and the concept of infinity and helps us intuitively comprehend these and other building blocks of mathematics by explaining their discovery and uses.
Keywords: Mathematics --Popular works